2019
DOI: 10.1103/physrevd.100.046016
|View full text |Cite
|
Sign up to set email alerts
|

Are nonperturbative AdS vacua possible in bosonic string theory?

Abstract: In this paper, following the work of Hohm and Zwiebach [arXiv:1905.06583], we show that in bosonic string theory nonperturbative anti-de Sitter (AdS) vacua could exist with all α ′ corrections included. We also discuss the possibility of the coexistence of nonperturbative dS and AdS vacua.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 24 publications
0
23
0
Order By: Relevance
“…In [21], the analogy in the Einstein frame is then discussed. In our recent work [22], we showed that similar stories occur for configurations depending on a single space coordinate, and non-perturbative Anti-de-Sitter (AdS) vacua are also allowed. Furthermore, we conjectured that the non-perturbative AdS and dS vacua might not be able to coexist in bosonic string theory.…”
Section: Jhep01(2020)164mentioning
confidence: 72%
“…In [21], the analogy in the Einstein frame is then discussed. In our recent work [22], we showed that similar stories occur for configurations depending on a single space coordinate, and non-perturbative Anti-de-Sitter (AdS) vacua are also allowed. Furthermore, we conjectured that the non-perturbative AdS and dS vacua might not be able to coexist in bosonic string theory.…”
Section: Jhep01(2020)164mentioning
confidence: 72%
“…In other words, higher derivative corrections are absorbed into redefined fields by O (d, d) invariant field redefinitions. In our recent work [11], we found that the JHEP05(2021)218 classification of α corrections also applies to space-dependent background (domain-wall ansatz). We also presented non-singular string cosmological solutions in refs.…”
Section: Jhep05(2021)218mentioning
confidence: 94%
“…It would be interesting to apply our result to specific examples. Higher-derivative corrections to Abelian T-duality have been applied in different contexts, such as corrections to entropy and black-hole solutions [89][90][91][92][93] and cosmological backgrounds [94][95][96]. Higher-derivative corrections to Yang-Baxter deformations were recently considered in [45].…”
Section: Jhep10(2020)002 5 Outlookmentioning
confidence: 99%